CK1δ stimulates ubiquitination‐dependent proteasomal degradation of ATF4 to promote chemoresistance in gastric Cancer. Issue 10 (14th October 2021) - Feng, Lifeng; Li, Muchun; Hu, Xinyang; Li, Yiling; Zhu, Liyuan; Chen, Miaoqin; Wei, Qi; Xu, Wenxia; Zhou, Qiyin; Wang, Weikai; Chen, Dingwei; Wang, Xian; et al.
Abstract: Chemoresistance remains a major obstacle to successful cancer therapy, especially for advanced cancers. It used to be recognised as a stable outcome resulting from genetic changes. However, recent studies showed that chemoresistance can also be unstable and reversible with the involvement of non‐genetic alterations. In the present study, we found that activating transcription factor 4 (ATF4) is downregulated in chemoresistant gastric cancer cells. The over‐expression of ATF4 reversed chemoresistance by activating CHOP transcription to enhance drug‐induced apoptosis, and vice versa. Moreover, casein kinase 1 delta (CK1δ) was identified as the kinase responsible for ATF4‐S219 phosphorylation, which triggered βTrCP‐mediated ATF4 polyubiquitination to promote its proteasomal degradation subsequently. Interestingly, drug withdrawal gradually restored chemosensitivity as well as ATF4 expression in chemoresistant cells, highlighting the dependence of dynamic drug resistance on ATF4 protein expression. In line with these findings, the inhibition of ATF4 protein degradation by CK1δ or proteasome inhibitors overcame chemoresistance both in vitro and in vivo. Taken together, these results indicate that CK1δ stimulates βTrCP‐dependent ATF4 polyubiquitination and subsequent proteasomal degradation to promote chemoresistance in gastric cancer. Stabilisation of the ATF4 protein with bortezomib (BTZ), an anticancer drug that inhibits proteasomal degradation, might be a rational strategy to improve chemotherapeutic efficacy in gastric cancer. Abstract : Chemoresistance could be unstable and reversible. ATF4 protein level is negatively correlated to chemoresistance in gastric cancer. CK1δ stimulates ATF4 poly‐ubiquitinated degradation is responsible for the dynamic chemoresistance. Targeting ATF4 could be a rational strategy to reverse chemoresistance in gastric cancer.